PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA KOMIK TERHADAP PENGETAHUAN SEKS EDUKASI USIA DINI MELALUI PENDEKATAN HOLISTIK KEBIDANAN - Selvy Apriani (LPPM Universitas Abdurrab, 2023)
Sexual violence is currently very high and rampant, based on data from the World Health Organization (WHO) it is estimated that around one billion children experience physical violence, sexual violence, psychological violence, injuries, become disordered and children aged 0 to 17 die as many as 40,150 due to violence globally. According to KPAI, there were 262 cases of sexual violence against children in 2019 and in 2020 it increased to 238 cases. In 2020, the Central Statistics Agency recorded 341 cases of sexual violence in South Sumatra. The high number of cases of sexual abuse that occur in children opens our eyes that there is still a lack of children's understanding of sex education. The use of Comic Media is a very fun learning medium for early childhood, the images in comics can animate a row of story texts so that they can easily convey messages to children about sex education in early childhood, so they can anticipate the dangers that will threaten them. The purpose of this study was to analyze the effect of health education using comic media on sex knowledge in early childhood education through a holistic midwifery approach. This research is a quasi-experimental study with one group pretest and posttest without control. Sampling was carried out by total sampling and univariate analysis using the T-dependent test. The results of this study indicate that there are differences in knowledge before and after being given educational sex comics with a p-value of 0.000. It is hoped that this research can contribute to sex education in children starting as early as possible and it is hoped that in the future there will be more media modifications that can be used to introduce sex from an early age to children.